Spotlight on databases - Gipp, Jennifer (Australia : Thomson Course Technology, 2007)
This book introduces middle school learners to basic technology concepts and skills through a computer application suite.
Chapter 1. Introduction to databases -- Chapter 2. Creating a database -- Chapter 3. Formatting and editing -- Chapter 4. Queries and reports
Includes index.
Keywords: COMPUTERS -- STUDY AND TEACHING (SECONDARY)